(untitled) (Annals of Medical Research, 2021)
Aim: Rotavirus is the most common cause of severe gastroenteritis in children. Rotavirus diarrhea can lead to complications of rotavirus-induced severe diarrhea death resulting in electrolyte imbalance and dehydration. Rotavirus vaccination is the most effective method of preventing severe rotavirus infection. The purpose of this study was to evaluate the knowledge levels and attitudes of primary health care providers physicians related to rotavirus vaccine, which is one of the vaccines not yet added to the vaccination schedule in Turkey.